log(x²) (x² - 2x + 1) ≤ 0
одз х ≠ 0 х ≠ 1 x ≠ -1
log(x²) (x² - 2x + 1) ≤ log(x²) 1
log(f) q ≤ log(f) g ⇔ (f - 1)(q - g) ≤ 0
(x² - 1) (x² - 2x + 1 - 1) ≤ 0
(x - 1)(x + 1)x(x - 2) ≤ 0
метод интервалов
[-1] [0] [1] [2]
учитываем одз
x ∈ (-1, 0) U (1, 2]
log(x²) (x² - 2x + 1) ≤ 0
одз х ≠ 0 х ≠ 1 x ≠ -1
log(x²) (x² - 2x + 1) ≤ log(x²) 1
log(f) q ≤ log(f) g ⇔ (f - 1)(q - g) ≤ 0
(x² - 1) (x² - 2x + 1 - 1) ≤ 0
(x - 1)(x + 1)x(x - 2) ≤ 0
метод интервалов
[-1] [0] [1] [2]
учитываем одз
x ∈ (-1, 0) U (1, 2]